The art of successful brand collaborations : partnerships with artists, designers, museums, territories, sports, celebrities, science, good causes, and more /: partnerships with artists, designers, museums, territories, sports, celebrities, science, good causes, and more. (2020) - Michel, Géraldine; Willing, Reine
No abstract available